1970
DOI: 10.1590/s0034-89101970000200001
|View full text |Cite
|
Sign up to set email alerts
|

Dispersão de Biomphalaria straminea, hospedeira intermediária do Schistosoma mansoni, através da distribuição de peixes

Abstract: Foi focalizado, pela primeira vez o encontro de B. straminea no Estado de São Paulo. Esta espécie vem juntar-se aos planorbídeos já assinalados em nosso Estado. Foram descritos os criadouros, onde a B. straminea foi coletada, localizados em tanques de criação de peixes nas Estações de Piscicultura de Barra Bonita e Americana, Estado de São Paulo, e em um aquário particular na capital dêsse Estado. Fêz-se referência ao transporte de peixes oriundos de zonas do país onde ocorre aquela espécie, Amazonas e Ceará, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1971
1971
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…10 , 1970). ABSTRACT: The present distribution of planorbid snails, the intermediate hosts of Schistosoma mansoni, in Pampulha lake (Belo Horizonte, Minas Gerais -Brazil) and the rapid dispersal of Biomphalaria tenagophila in the lake perimeter are described.…”
Section: Resultsmentioning
confidence: 99%
“…10 , 1970). ABSTRACT: The present distribution of planorbid snails, the intermediate hosts of Schistosoma mansoni, in Pampulha lake (Belo Horizonte, Minas Gerais -Brazil) and the rapid dispersal of Biomphalaria tenagophila in the lake perimeter are described.…”
Section: Resultsmentioning
confidence: 99%
“…act as the first intermediate hosts (Ostrowski de Núñez, 1977, 1982; Violante-González et al , 2009), and fish serve as second intermediate hosts (Karvonen et al , 2006). Several species of Biomphalaria have been registered in São Paulo State (Corrêa et al , 1970), and Biomphalaria straminea (Dunker, 1848) and Biomphalaria gabrata (Say, 1818) have been recorded in the drainage basin of the Paranapanema River (Corrêa et al , 1970; Teles & Vaz, 1987). In addition, Oliveira & Krau (1970), Barbosa (1983) and Callisto et al (2005) reported a positive association between Biomphalaria molluscs and environments rich in organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Ao que as observações sugerem, o aparecimento desses moluscos estaria relacionado com a introdução de plantas aquáticas e peixes nesses locais, conforme já relatado por Correa e col. 2 ,1970.…”
Section: Discussionunclassified